Middle East Respiratory Syndrome Coronavirus (MERS-CoV) in Dromedary Camels in Africa and Middle East - Kandeil, Ahmed; Gomaa, Mokhtar; Nageh, Ahmed; Shehata, Mahmoud M.; Kayed, Ahmed E.; Sabir, Jamal S. M.; Abiadh, Awatef; Jrijer, Jamel; Amr, Zuhair; Abi Said, Mounir; Byarugaba, Denis K.; Wabwire-Mangen, Fred; et al. (Viruses, 2019)
Dromedary camels are the natural reservoirs of the Middle East respiratory syndrome coronavirus (MERS-CoV). Camels are mostly bred in East African countries then exported into Africa and Middle East for consumption. To understand the distribution of MERS-CoV among camels in North Africa and the Middle East, we conducted surveillance in Egypt, Senegal, Tunisia, Uganda, Jordan, Saudi Arabia, and Iraq. We also performed longitudinal studies of three camel herds in Egypt and Jordan to elucidate MERS-CoV infection and transmission. Between 2016 and 2018, a total of 4027 nasal swabs and 3267 serum samples were collected from all countries. Real- time PCR revealed that MERS-CoV RNA was detected in nasal swab samples from Egypt, Senegal, Tunisia, and Saudi Arabia. Microneutralization assay showed that antibodies were detected in all countries. Positive PCR samples were partially sequenced, and a phylogenetic tree was built. The tree suggested that all sequences are of clade C and sequences from camels in Egypt formed a separate group from previously published sequences. Longitudinal studies showed high seroprevalence in adult camels. These results indicate the widespread distribution of the virus in camels. A systematic active surveillance and longitudinal studies for MERS-CoV are needed to understand the epidemiology of the disease and dynamics of viral infection.